Are voiding parameters a marker for the severity of quality of life impairment in women with overactive bladder symptoms?. Issue 6 (24th October 2016) - Basu, Maya; Doumouchtsis, Stergios K.
Abstract : Aims: There is evidence of an association between voiding parameters and the presence of overactive bladder symptoms. The aim of this study was to evaluate whether there is any association between pressure flow study parameters and the degree of health related quality of life impairment in women with OAB symptoms. The null hypothesis is that there is no significant correlation between quality of life domain scores and pressure flow study parameters. Methods: One hundred and sixty‐seven consecutive women with overactive bladder symptoms underwent evaluation with a quality of life assessment plus filling and voiding cystometry. These data were used to evaluate for any correlation between pressure flow study parameters and quality of life domain scores. Results: Fifty‐six out of 167 women had proven detrusor overactivity (DO). There were no differences in voiding parameters or quality of life scores between women with DO and women without DO. There was no consistent correlation identified between quality of life domain scores and pressure flow variables. Conclusions: There is no evidence of an association between increasing quality of life impairment and voiding parameters in this cohort.